The rice LRR-like1 protein YELLOW AND PREMATURE DWARF 1 is involved in leaf senescence induced by high light. (17th November 2020) - Chen, Dongdong; Qiu, Zhennan; He, Lei; Hou, Linlin; Li, Man; Zhang, Guangheng; Wang, Xiaoqi; Chen, Guang; Hu, Jiang; Gao, Zhenyu; Dong, Guojun; Ren, Deyong; et al.
Abstract: Senescence in plants is induced by endogenous physiological changes and exogenous stresses. In this study, we isolated two alleles of a novel rice ( Oryza sativa ) mutant, yellow and premature dwarf 1 ( ypd1 ). The ypd1 mutants exhibited a yellow and dwarf phenotype from germination, and premature senescence starting at tillering. Moreover, the ypd1 mutants were sensitive to high light, which accelerated cell death and senescence. Consistent with their yellow phenotype, the ypd1 mutants had abnormal chloroplasts and lower levels of photosynthetic pigments. TUNEL assays together with histochemical staining demonstrated that ypd1 mutants showed cell death and that they accumulated reactive oxygen species. The ypd1 mutants also showed increased expression of genes associated with senescence. Map-based cloning revealed a G→A substitution in exon 6 ( ypd1-1 ) and exon 13 ( ypd1-2 ) of LOC_Os06g13050 that affected splicing and caused premature termination of the encoded protein. YPD1 was found to be preferentially expressed in the leaf and it encodes a LRR-like1 protein. Complementation, overexpression, and targeted deletion confirmed that the mutations in YPD1 caused the ypd1 phenotype. YPD1 was localized on the chloroplast membrane. Our results thus demonstrate that the novel rice LRR-like1 protein YPD1 affects chloroplast development and leaf senescence. Abstract : A novel rice LRR-like1 protein, YELLOW AND PREMATURE DWARF 1, affects chloroplast development and is involved in leaf senescence induced by high light.